The effects of procedures on social interaction: A literature review - Vanessa Mertins (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2008)
While economists have neglected procedures for a long time, other social scientists early established a substantial research program. By now, there exists a large gap between a sheer bulk of empirical, experimental, and theoretical studies by non-economists and the fact that there is hardly any economic research on procedures. We argue that due to clear evidence for procedures influencing human decision-making, economists can not remain silent about procedural aspects of strategic interactions any longer. There is an important research agenda to be developed. This survey article is intended to discuss an important approach by which the standard economic model, which is based on consequentialist preferences, needs to be enriched: not only outcomes shape human behavior but also the way in which decisions are taken. Behavioral economics may serve as an important link. Its aim is to integrate insights of cognitive and social psychologists as well as experimental economists with neoclassical economic theory. We argue that experimental economics should increase its efforts to identify procedural effects and that these experiments should be more incorporated in the theoretical literature as part of an ongoing dialogue between theorists and experimentalists. Among procedural aspects, procedural fairness suggests itself to become an integrative part. To highlight the need for rethinking the standard economic approach we review social science literature on procedural effects, with a special focus on experimental economics and inspired theory-building.
Keywords: 330